Investigating EFL Students’ Tense Errors in Writing Narrative Text - Veneza Firda Resita Fanny; Juhansar Juhansar; Ulfa Amalia; Ari Prasetyoaji (Universitas Teknologi Yogyakarta, 2022)
A narrative text should have a generic structure and language feature. Simple past tense is a language feature of the text. In writing an English narrative text, EFL students commonly make errors related to using the simple past tense. Therefore, this research aims to discover EFL students’ types of errors in writing narrative text using simple past and to determine EFL students’ dominant errors in writing narrative text using the simple past tense. The design of this research is a mixed-method. The respondents are ten third-semester EFL students of the English Language Education Department of Universitas Teknologi Yogyakarta. Research data were documents, EFL students' narrative text writing-related Cross-Cultural Understanding, taken from the subject's lecturer. Data were analyzed qualitatively and quantitatively. The results of this research show that EFL students made four types of errors: omission, addition, misformation, and misordering, in writing narrative text using the simple past tense. This research reveals 123 EFL students’ errors in writing narrative text using the simple past tense. Misformation was the most dominant error with 100 errors (81%), followed by addition with 12 errors (10%), omission with 9 errors (7%), and misordering with 2 errors (2%). This research has a small scope, limited to analyzing third-semester EFL students’ errors in writing narrative text using simple past tense at Universitas Teknologi Yogyakarta. Therefore, further researchers are expected to conduct wide-scope research, such as Indonesian EFL students using a different research design, e.g., experimental research on the effective technique used to decrease EFL students’ errors in writing narrative text using the simple past tense.